Dual role of the active site 'lid' regions of protochlorophyllide oxidoreductase in photocatalysis and plant development. (14th September 2020) - Zhang, Shaowei; Godwin, Alan R. F.; Taylor, Aoife; Hardman, Samantha J. O.; Jowitt, Thomas A.; Johannissen, Linus O.; Hay, Sam; Baldock, Clair; Heyes, Derren J.; Scrutton, Nigel S.
Abstract : Protochlorophyllide oxidoreductase (POR) catalyses reduction of protochlorophyllide (Pchlide) to chlorophyllide, a light‐dependent reaction of chlorophyll biosynthesis. POR is also important in plant development as it is the main constituent of prolamellar bodies in etioplast membranes. Prolamellar bodies are highly organised, paracrystalline structures comprising aggregated oligomeric structures of POR–Pchlide–NADPH complexes. How these oligomeric structures are formed and the role of Pchlide in oligomerisation remains unclear. POR crystal structures highlight two peptide regions that form a 'lid' to the active site, and undergo conformational change on binding Pchlide. Here, we show that Pchlide binding triggers formation of large oligomers of POR using size exclusion chromatography. A POR 'octamer' has been isolated and its structure investigated by cryo‐electron microscopy at 7.7 Å resolution. This structure shows that oligomer formation is most likely driven by the interaction of amino acid residues in the highly conserved lid regions. Computational modelling indicates that Pchlide binding stabilises exposure of hydrophobic surfaces formed by the lid regions, which supports POR dimerisation and ultimately oligomer formation. Studies with variant PORs demonstrate that lid residues are involved in substrate binding and photocatalysis. These highly conserved lid regions therefore have a dual function. The lid residues position Pchlide optimally to enable photocatalysis. Following Pchlide binding, they also enable POR oligomerisation – a process that is reversed through subsequent photocatalysis in the early stages of chloroplast development. Abstract : The structure of light‐dependent protochlorophyllide oxidoreductase (POR) suggests that amino acid residues in highly conserved active site 'lid' regions are responsible for POR oligomer formation. This is confirmed by cryo‐EM of POR–NADPH–Chlide complexes and computational modelling. Studies with variant PORs demonstrate that lid residues are also involved in substrate binding and photocatalysis.